New differentiability criteria for complex-valued functions - Alikulov, E. O. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A theorem is proved which states that the existence of the asymptotic limit of f_z as z → z_0 implies that the complex-valued function f(z) is R-differentiable at z_0.